Literature Review: Helminthiasis pada Kehamilan - Cahyani, Faradhila Azqiah; Septiani, Linda; Mutiara, Hanna; Suwandi, Jhons Fatriyadi (Medula, 2024)
Helminthiasis is a disease caused by intestinal nematode worms that are transmitted through soil orSoil Transmitted Helminth (STH). The types of STH are:Ascaris lumbricoides, Trichuris trichiura, Ancylostoma duodenale, and Necator americanus. Helminthiasis has infected as many as 1.5 billion of the world's population. Helminthiasis is often found in countries with tropical, subtropical climates and countries that are still categorized as poor. Helminthiasis falls into the categoryNeglected Tropical Disease (NTD) which if left untreated can cause health problems. Purpose ofliterature review This provides a review of the epidemiology, clinical manifestations, necessary examinations, and management of helminthiasis, especially in pregnant women. This research uses a literature study method from 2016-2023. The results of this literature study show that clinical manifestations are influenced by the severity or lightness of the infection, gold standardTo find out the incidence of helminthiasis is to do a stool examination, and helminthiasis can be treated by providing care servicesantenatal care. The conclusion is that helminthiasis in pregnant women can affect the condition of the mother and fetus in the womb.